ESR and CRP Diagnostic Thresholds for Prosthetic Joint Infection in Hip Hemiarthroplasty - Warren, Jared A.; Scotting, Oliver; Anis, Hiba K.; Bircher, James; Klika, Alison K.; Kamath, Atul F.; Piuzzi, Nicolas S.; Higuera, Carlos A. (The Journal of Hip Surgery, 2020)
Diagnostic thresholds used to standardize the definition for prosthetic joint infection (PJI) have largely focused on total joint arthroplasty (TJA). Established PJI thresholds exist for serum erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) in TJA; however, they do not exist for revision hip hemiarthroplasty (rHHA). The purpose of this study was to establish thresholds for (1) ESR and (2) CRP to diagnose PJI in rHHA. Data were collected on a prospective cohort of 69 rHHA patients undergoing orthopaedic surgery between 1/2017 and 2/2019 in a single health care system. Procedures were categorized as septic or aseptic revisions using Musculoskeletal Infection Society (MSIS) criteria (2013). There were 44 ESRs (n = 28 aseptic, n = 16 septic) and 46 CRPs (n = 29 aseptic, n = 17 septic) available for analysis. Two tailed t-tests were performed to compare the mean ESR and CRP in aseptic and septic cases. Receiver operator characteristic (ROC) curves were generated to obtain diagnostic cutoff thresholds using the Youden's Index (J) for ESR and CRP. The mean ESR was 50.3 ± 30.6 mm/h versus 15.4 ± 17.7 mm/h (p < 0.001), while the mean CRP was 29.9 ± 24.8 mg/L versus 4.1 ± 8.2 mg/L (p < 0.001) for septic and aseptic revisions, respectively. The diagnostic threshold for PJI determined by the ROC curve was 44 mm/h for ESR (sensitivity = 56.3%; specificity = 100.0%; J = 0.563; area under the curve (AUC) = 0.845), while it was 12.5 mg/L for CRP (sensitivity = 70.6%; specificity = 96.6%; J = 0.672; AUC = 0.896). For patients with HHA, an ESR of 44 mm/h was and a CRP of 12.5 mg/L was highly specific for PJI. The thresholds are similar to the MSIS thresholds currently published. Larger prospective trials are needed to establish more robust and conclusive diagnostic criteria for PJI in HHA, including investigations not only of ESR and CRP but synovial white blood cell count and synovial polymorphonuclear leukocytes % as well.
Keywords: PJI; hemiarthroplasty; ESR; CRP; diagnostics; revision